Multi-scale isotopic heterogeneity reveals a complex magmatic evolution: An example from the wallundry suite granitoids of the lachlan fold belt, Australia - Iles, Kieran A.; Hergt, Janet M.; Woodhead, Jon D. (Frontiers in Earth Science, 2023)
Open-system magmatic processes are expected to impart various sorts of isotopic heterogeneity upon the igneous rocks they produce. The range of processes under the “open-system” umbrella (e.g., simple two-component mixing, magma mingling, assimilation with fractional crystallization) cannot usually be uniquely identified using data from a single isotope system. The use of bulk-rock, mineral separate and in situ techniques and multiple isotope systems allows the characterization of isotopic variability at different sampling scales, illuminating details of the petrogenesis of a magmatic system. This approach has been applied to granitoids of the Wallundry Suite in the Lachlan Fold Belt, Australia. The Wallundry Suite exhibits variations in mineral assemblage, mineral composition and trends in bulk-rock major and trace element compositions consistent with the involvement of liquid-crystal sorting processes such as fractional crystallization. In situ paired O-Hf isotope data from zircon in 6 samples show an array indicating the isotopic evolution of the melt phase. Similarly, bulk-rock Sr-Nd-Hf isotope arrays support open-system magma evolution. These data combined with the petrographic observations and major and trace element geochemical variations suggest some form of assimilation-fractional crystallization (AFC) process in the petrogenesis of the Wallundry Suite. Added complexity is revealed by two observations: (1) the isotopic variations are only weakly coupled to the lithology and major element compositions of the samples; and (2) there are distinguishable differences between the Hf isotope compositions of bulk-rock samples and those of the magmatic zircons they host. To varying degrees the rocks consistently show negative ΔεHfbulk-zrc values (i.e., the bulk-rock compositions have less radiogenic Hf isotope values than their coexisting zircons). The preservation of distinctly low Nd and Hf isotope ratios in an Fe-Ti oxide mineral separate suggests that the bulk-rock vs zircon discrepancy is caused by the presence of unmelted components derived from a contaminant of continental origin (i.e., a rock with low Sm/Nd and Lu/Hf and thus unradiogenic Nd and Hf). Evidently, a complex interplay of assimilation, crystallization and melt segregation is required to account for the data. This investigation demonstrates that such complexity can, nevertheless, be disentangled through comparison of complementary isotope data at multiple sampling scales.